Electronic transport in molecular systems - Souza, Aldilene Saraiva (2012)
The thesis presents the treoretical studies of electronic transport in molecular devices for two different systems. Firstly we report a comparison between modeling and experi mental current-voltage characteristics of self-assembled monolayers of 5- (4-pyridine)-1,3,4- oxadiazole-2-thiol (HPYT) and 5-(4-phenyl)-1,3,4-oxadiazole-2-thiol (HPOT) molecules deposi ted on A u (111) . The formation of these self-assembled monolayers was confirmed by scanning tunneling microscopy (STM) measurements. DFT calculations were per formed to obtain the most stable conformation of the molecular film. To compare with these results, STM images were calculated using a model based on a master equation technique. Striking similarity was found between the calculated and measured STM im ages, thus indicating the applicability of the model. From this comparison, we suggest that both HPYT and HPOT thiol molecules are attached to the Au surface by a bond between the sulfur and single gold atoms . A simple quantum model is proposed for describing the tunneling current along the molecular monolayer assembly on the Au(111) surface. Secondly we investigate spin transport properties in a junction composed of a polyacety lene chain bridging two zigzag graphene nanoribbon (ZGNRs) electrodes. The transport calculations are carried out using a non-equilibrium Green's function (NEGF) technique combined with density functional theory (DFT). Previous works have demonstrated that the ZGNRs exhibit a special antiferromagnetic (AF) ordering and half-metallicity at edge states, which can both be destroyed by applying a strong externai electric field. Here we demonstrate that the connection between the molecular bridge and non-equivalent carbon atoms (A / B) in the graphene sublattice of ZGNRs may occur in two bonding arrangements and can produce metallic and semiconducting systems strongly dependent on the local coupling. By considering the carbon ring where the chain is linked, one connection resembles a para-linkage in benzene, whereas the other connection is similar to a meta-linkage. This results in different conductances for these configurations, which may be controlled by field-effect gating. Finally, the spin filter efficiency for these sys tems as a function of electric field is discussed. We also demonstrated that donor (D) and acceptor (A) groups attached to molecular bridge offer the possibility to modify the trans mission probability of para-linkage and meta-linkage systems in a controlled way with a destructive quantum interference (QI) effective. In our calculation was demonstrated it is possible, for instance, by introducing the DA groups with magnetic properties and keep the spin polarized , such that spin-up and spin-down orbitais have different energies. This facilitates the construction of a spin valve that lets either spin-up or spin-down electrons to move while one is blocked. Abstract The thesis presents the treoretical studies of electronic transport in molecular devices for two different systems. Firstly we report a comparison between modeling and experi mental current-voltage characteristics of self-assembled monolayers of 5- (4-pyridine)-1,3,4- oxadiazole-2-thiol (HPYT) and 5-(4-phenyl)-1,3,4-oxadiazole-2-thiol (HPOT) molecules deposi ted on A u (111) . The formation of these self-assembled monolayers was confirmed by scanning tunneling microscopy (STM) measurements. DFT calculations were per formed to obtain the most stable conformation of the molecular film. To compare with these results, STM images were calculated using a model based on a master equation technique. Striking similarity was found between the calculated and measured STM im ages, thus indicating the applicability of the model. From this comparison, we suggest that both HPYT and HPOT thiol molecules are attached to the Au surface by a bond between the sulfur and single gold atoms . A simple quantum model is proposed for describing the tunneling current along the molecular monolayer assembly on the Au(111) surface. Secondly we investigate spin transport properties in a junction composed of a polyacety lene chain bridging two zigzag graphene nanoribbon (ZGNRs) electrodes. The transport calculations are carried out using a non-equilibrium Green's function (NEGF) technique combined with density functional theory (DFT). Previous works have demonstrated that the ZGNRs exhibit a special antiferromagnetic (AF) ordering and half-metallicity at edge states, which can both be destroyed by applying a strong externai electric field. Here we demonstrate that the connection between the molecular bridge and non-equivalent carbon atoms (A / B) in the graphene sublattice of ZGNRs may occur in two bonding arrangements and can produce metallic and semiconducting systems strongly dependent on the local coupling. By considering the carbon ring where the chain is linked, one connection resembles a para-linkage in benzene, whereas the other connection is similar to a meta-linkage. This results in different conductances for these configurations, which may be controlled by field-effect gating. Finally, the spin filter efficiency for these sys tems as a function of electric field is discussed. We also demonstrated that donor (D) and acceptor (A) groups attached to molecular bridge offer the possibility to modify the trans mission probability of para-linkage and meta-linkage systems in a controlled way with a destructive quantum interference (QI) effective. In our calculation was demonstrated it is possible, for instance, by introducing the DA groups with magnetic properties and keep the spin polarized , such that spin-up and spin-down orbitais have different energies. This facilitates the construction of a spin valve that lets either spin-up or spin-down electrons to move while one is blocked.